2014
DOI: 10.1590/s1516-89132014000100010
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of new steroids of Kala Dhaman grass (Cenchrus setigerus) and evaluation of their bioactivity

Abstract: The present study was carried out to determine the possible bioactive components (steroids) -stigmasta-4,22-dien-3-one(4.93%), δ4-sitosterol-3-one (stigmast-4-en-3-one)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…This grass is gaining attention in various field of research as it is more competitive in high temperature, solar radiation and low moisture. It is most suitable and highly nutritive grass for environmental conditions of desert 7 .…”
Section: Introductionmentioning
confidence: 99%
“…This grass is gaining attention in various field of research as it is more competitive in high temperature, solar radiation and low moisture. It is most suitable and highly nutritive grass for environmental conditions of desert 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The existence of steroid compounds has previously been documented in different parts of Censchrus spp. (Singariya et al, 2012(Singariya et al, , 2014. Therefore, the presence of different bioactive steroid compounds could be speculated in C. pennnisetiformis as well that probably confer resistance against F. oxysporum.…”
Section: Resultsmentioning
confidence: 99%
“…Other authors, including Haider et al [ 35 ] and Jasso de Rodríguez et al [ 36 ], isolated this compound in other plant species, Adiantum capillus -Veneris and Psacalium paucicapitatum , respectively. This compound (Ethyl iso-allocholate) of steroidal nature has been reported as a potential therapeutic agent, as it has diuretic, anti-inflammatory, anticancer and antimicrobial activities [ 35 , 36 , 37 ]. Chokki et al [ 6 ] also reported that the antimicrobial activity observed with these plants would be attributed to their chemical composition.…”
Section: Discussionmentioning
confidence: 99%